Demand Player Sovereignty - Solo, Liz (InTensions, 2014)
Demand Player Sovereignty or DPS is a civil disobedience movement originated by the Third Faction collective. The goal of DPS is to subvert the deliberate factional conflict within Azeroth while drawing parallels to synthetic manufactured conflicts taking place in the world at large. DPS host quests and interventions both in the real world and the World of Warcraft. See http://www.thirdfaction.org/ www.lizsolo.com Machinima by Liz Solo. Text by Thomas Asmuth with the Third Faction. Created with and for the Third Faction. Originally screened at ISEA Istanbul 2011.